Genomic Signatures for Species-Specific Adaptation in Lake Victoria Cichlids Derived from Large-Scale Standing Genetic Variation. (21st March 2021) - Nakamura, Haruna; Aibara, Mitsuto; Kajitani, Rei; Mrosso, Hillary D J; Mzighani, Semvua I; Toyoda, Atsushi; Itoh, Takehiko; Okada, Norihiro; Nikaido, Masato
Abstract: The cichlids of Lake Victoria are a textbook example of adaptive radiation, as >500 endemic species arose in just 14, 600 years. The degree of genetic differentiation among species is very low due to the short period of time after the radiation, which allows us to ascertain highly differentiated genes that are strong candidates for driving speciation and adaptation. Previous studies have revealed the critical contribution of vision to speciation by showing the existence of highly differentiated alleles in the visual opsin gene among species with different habitat depths. In contrast, the processes of species-specific adaptation to different ecological backgrounds remain to be investigated. Here, we used genome-wide comparative analyses of three species of Lake Victoria cichlids that inhabit different environments— Haplochromis chilotes, H. sauvagei, and Lithochromis rufus —to elucidate the processes of adaptation by estimating population history and by searching for candidate genes that contribute to adaptation. The patterns of changes in population size were quite distinct among the species according to their habitats. We identified many novel adaptive candidate genes, some of which had surprisingly long divergent haplotypes between species, thus showing the footprint of selective sweep events. Molecular phylogenetic analyses revealed that a large fraction of the allelic diversity among Lake Victoria cichlids was derived from standing genetic variation that originated before the adaptive radiation. Our analyses uncovered the processes of species-specific adaptation of Lake Victoria cichlids and the complexity of the genomic substrate that facilitated this adaptation.